Index coronary angiography use in Manitoba, Canada: a population-level descriptive analysis of First Nations and non-First Nations recipients. Issue 3 (25th March 2018) - Schultz, Annette S H; Dahl, Lindsey; McGibbon, Elizabeth; Brownlie, R Jarvis; Cook, Catherine; Elbarouni, Basem; Katz, Alan; Nguyen, Thang; Sawatzky, Jo Ann; Sinclaire, Moneca; Throndson, Karen; Fransoo, Randy
Abstract : Objectives: To investigate recipient characteristics and rates of index angiography among First Nations (FN) and non-FN populations in Manitoba, Canada. Setting: Population-based, secondary analysis of provincial administrative health data. Participants: All adults 18 years or older who received an index angiogram between 2000/2001 and 2008/2009. Primary and secondary outcome measures: (1) Descriptive statistics for age, sex, income quintile by rural and urban residency and Charlson Comorbidity Index for FN and non-FN recipients. (2) Annual index angiogram rates for FN and non-FN populations and among those rates of 'urgent' angiograms based on acute myocardial infarction (AMI)-related hospitalisations during the previous 7 days. (3) Proportions of people who did not receive an angiogram in the 20 years preceding an ischaemic heart disease (IHD) diagnosis or a cardiovascular death; stratified by age (<65 or ≥65 years old). Results: FN recipients were younger (56.3vs63.8 years; p<0.0001) and had higher Charlson Comorbidity scores (1.32vs0.78; p<0.001). During all years examined, index angiography rates were lower among FN people (2.67vs3.33 per 1000 population per year; p<0.001) with no notable temporal trends. Among the index angiogram recipients, a higher proportion was associated with an AMI-related hospitalisation in the FN group (28.8%vs25.0%; p<0.01) and in both groups rates significantly increased over time. FN people who died from cardiovascular disease or were older (65+years old) diagnosed with IHD were more likely to have received an angiogram in the preceding 20–30 years (17.8%vs12.5%; p<0.01 and 50.9%vs49.5%; p<0.03, respectively). FN people diagnosed with IHD who were under the age of 65 were less likely to have received an angiogram (47.8%vs53.1%; p<0.01) Conclusions: Index angiogram use differences are suggested between FN and non-FN populations, which may contribute to reported IHD disparities. Investigating factors driving these rates will determine any association between ethnicity and angiography services.